Solid-state battery pack and processing method thereof
By surface modification of the polymer matrix and inorganic filler, liquid electrolyte infiltrates under the action of electric field, combined with heat treatment and stress regulation, the problem of uneven infiltration of solid electrolyte membrane in solid battery packs is solved, and a more stable structure and higher ion transport performance are achieved.
Patent Information
- Application Number
- CN202510295224.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The existing hybrid solid electrolyte membranes have problems of uneven infiltration and easy to produce microscopic voids when infiltrating liquid electrolytes in an open environment.
By surface modification of the polymer matrix and inorganic filler, a mixed solid electrolyte membrane was prepared, and liquid electrolyte was infiltrated under the action of an electric field. The electric field parameters were adjusted according to the ion concentration distribution and solvent diffusion data, followed by heat treatment and stress regulation, and finally laminated with the self-supporting electrode to construct a nanointerface layer.
The uniform infiltration of hybrid solid electrolyte membranes is achieved, the formation of microscopic voids is reduced, the structural stability and ion transport performance of the membrane are improved, and the safety and life bottlenecks caused by infiltration unevenness and microscopic defect accumulation are solved.
Smart Images

Figure CN119812445A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state battery preparation, and in particular to a solid-state battery pack and a processing method thereof. Background Art
[0002] In recent years, with the increasing demand for high safety, high energy density and bendability in wearable and flexible electronic devices, researchers have gradually turned their attention to the application of "hybrid solid polymer electrolytes (HSEM)" in flexible batteries. Specifically, the usual practice is to use a polymer matrix (such as PVDF-HFP) to provide toughness and plasticity, and then disperse inorganic fillers (such as LLZTO) and an appropriate amount of lithium salt (such as LiTFSI) into it to construct a composite electrolyte membrane with both high ionic conductivity and mechanical stability. At the same time, in terms of electrodes, if self-supporting electrodes designed with carbon nanotube skeletons or other conductive skeletons are further used, flexible solid-state batteries with high rate charge and discharge and high cycle life can be initially realized at room temperature.
[0003] However, in the actual preparation process, some process links have technical difficulties. For example, in order to improve the ion transfer between the membrane and the electrode, the solid membrane is often "surface activated" or impregnated with a very small amount of liquid electrolyte in an open environment. Although the operation seems simple, due to the influence of various factors such as environmental humidity, oxygen, and polymer / inorganic filler interfacial tension, the wetting process is often uneven: some areas absorb more solvent and swell excessively, while other areas are insufficiently infiltrated due to local rejection or too fast drying speed. The resulting microscopic voids are often hidden deep in the membrane layer and are not easily exposed immediately in conventional tests (such as SEM, XRD, etc.). In addition, trace moisture and oxygen in the air may also react with lithium salts or fillers, further causing local chemical instability. These defects are often not obvious in early electrochemical tests, but after multiple thermal cycles or repeated bending, they will gradually amplify due to stress concentration and accumulation of side reactions, eventually causing ion transmission obstruction, rapid capacity decay, and even safety hazards. Since this process step involves precise control of environmental conditions and solvent evaporation behavior, and is closely related to the microstructure of HSEM, it is difficult for existing technologies to balance large-scale process simplification with stringent protection requirements, thus forming a difficult-to-overcome technical bottleneck. Summary of the invention
[0004] The main purpose of the present invention is to solve the technical problems that the existing hybrid solid electrolyte membrane is not uniformly infiltrated and easily generates microscopic gaps when being infiltrated with liquid electrolyte in an open environment.
[0005] A first aspect of the present invention provides a method for processing a solid-state battery pack, the method comprising: The polymer matrix and the inorganic filler are subjected to surface modification treatment, and the modified inorganic filler is dispersed in the modified polymer matrix to prepare a hybrid solid electrolyte membrane; Infiltrating the hybrid solid electrolyte membrane with liquid electrolyte under the action of an electric field, adjusting electric field parameters according to ion concentration distribution and solvent diffusion data during the infiltration process, to obtain a uniformly infiltrated hybrid solid electrolyte membrane; Performing heat treatment and stress control on the uniformly infiltrated hybrid solid electrolyte membrane to obtain a hybrid solid electrolyte membrane with a stable structure; A nano interface layer is constructed on the surface of the self-supporting electrode, and the structurally stable hybrid solid electrolyte membrane is laminated with the self-supporting electrode to obtain a flexible solid-state battery pack.
[0006] Optionally, the surface modification treatment of the polymer matrix and the inorganic filler includes: Polyvinylidene fluoride-hexafluoropropylene copolymer is selected as the polymer matrix, and lithium lanthanum zirconium titanium oxide is selected as the inorganic filler; The surface of the lithium lanthanum zirconium titanium oxide is activated by oxygen plasma to adjust the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide, and then the surface of the lithium lanthanum zirconium titanium oxide is coordinated and modified by a silane coupling agent to obtain a surface-modified lithium lanthanum zirconium titanium oxide; The quaternary ammonium salt group is introduced into the molecular chain of the polyvinylidene fluoride-hexafluoropropylene copolymer by peroxide-initiated grafting, and then the polyvinylidene fluoride-hexafluoropropylene copolymer is selectively fluorinated to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
[0007] Optionally, the peroxide-initiated grafting is used to introduce quaternary ammonium salt groups into the molecular chains of the polyvinylidene fluoride-hexafluoropropylene copolymer, and then the polyvinylidene fluoride-hexafluoropropylene copolymer is selectively fluorinated to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer, comprising: The polyvinylidene fluoride-hexafluoropropylene copolymer is dissolved in tetrahydrofuran, benzoyl peroxide is added as an initiator, and γ-methacryloxypropyltrimethoxysilane is added as an interface coupling agent, and the mixture is stirred and reacted at 60-70° C. for 2-3 hours to obtain a prepolymer having active sites; Adding dimethacryloyloxyethyl dodecyldimethyl quaternary ammonium salt monomer to the prepolymer having active sites, controlling the mass ratio of the quaternary ammonium salt monomer to the polyvinylidene fluoride-hexafluoropropylene copolymer to be 1:4 to 1:3, reacting at 75-85° C. for 4-6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer grafted with a quaternary ammonium salt group; The quaternary ammonium salt group-grafted polyvinylidene fluoride-hexafluoropropylene copolymer solution is cooled to 25-35° C., and a selective fluorination treatment is performed in a fluorine gas atmosphere with a controllable concentration gradient, wherein the fluorine gas volume fraction is distributed in a gradient of 20%:10%:5% from the surface layer to the inner layer, and the fluorination time is controlled to be 30-45 minutes to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
[0008] Optionally, the surface activation of the lithium lanthanum zirconium titanium oxide is performed by oxygen plasma, the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide is regulated, and then the surface coordination modification of the lithium lanthanum zirconium titanium oxide is performed by a silane coupling agent to obtain a surface-modified lithium lanthanum zirconium titanium oxide, comprising: The lithium lanthanum zirconium titanium oxide is dispersed in anhydrous ethanol, pretreated for 2-3 hours under an inert atmosphere, and then treated with oxygen plasma at a power of 50W-100W, with the oxygen flow rate controlled to be 20-30sccm for a treatment time of 15-30 minutes, and the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide is regulated by adjusting the ratio of plasma power to oxygen flow rate, and then dried under a vacuum environment for 4-6 hours to obtain a surface-activated lithium lanthanum zirconium titanium oxide; Under an inert atmosphere, a γ-glycidyloxypropyltrimethoxysilane coupling agent is dissolved in anhydrous tetrahydrofuran, and the surface-activated lithium lanthanum zirconium titanium oxide is added, and the mass ratio of the coupling agent to the lithium lanthanum zirconium titanium oxide is controlled to be 1:10 to 1:8. The reaction is stirred at 40-50° C. for 2-3 hours, and the mixture is centrifugally washed with anhydrous ethanol for 3-4 times and then vacuum dried at 60-70° C. for 8-12 hours to obtain a surface-modified lithium lanthanum zirconium titanium oxide.
[0009] Optionally, the modified inorganic filler is dispersed in the modified polymer matrix to prepare a hybrid solid electrolyte membrane, comprising: Dispersing the surface-modified lithium lanthanum zirconium titanium oxide in N-methylpyrrolidone, adding ferrocene as a dispersion stabilizer to the obtained basic dispersion, controlling the mass ratio of ferrocene to the surface-modified lithium lanthanum zirconium titanium oxide to be 1:50 to 1:30, and dispersing under ultrasonic conditions for 2-3 hours to obtain a first dispersion; Dissolving the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer in the first dispersion, controlling the mass fraction of the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer to be 15wt%-20wt%, and stirring uniformly at 60-70°C for 4-6 hours to obtain a uniform dispersion; The uniform dispersion is coated with an automatic coating machine at a coating speed of 2-4 mm / s and the substrate temperature is controlled at 40-50°C to obtain a wet film, which is then transferred to a vacuum oven and dried at 50°C for 4-6 hours and then at 80°C for 8-12 hours to obtain a hybrid solid electrolyte membrane.
[0010] Optionally, the hybrid solid electrolyte membrane is infiltrated with a liquid electrolyte under the action of an electric field, and electric field parameters are adjusted according to ion concentration distribution and solvent diffusion data during the infiltration process to obtain a uniformly infiltrated hybrid solid electrolyte membrane, including: dissolving lithium trifluoromethanesulfonyl diimide in a mixed solvent of ethylene carbonate and dimethyl carbonate, controlling the volume ratio of the ethylene carbonate to the dimethyl carbonate to be 1:1, and controlling the concentration of the lithium trifluoromethanesulfonyl diimide to be 1 mol / L, to obtain a liquid electrolyte; Under an environment of 35° C. and a relative humidity of 40%, a temperature and humidity gradient field is constructed around the hybrid solid electrolyte membrane, so that the temperature is distributed in a gradient from 35° C. to 25° C. from the inside to the outside, and the relative humidity is distributed in a gradient from 40% to 20% from the inside to the outside, and the temperature and humidity distribution data on the surface of the hybrid solid electrolyte membrane are obtained; According to the temperature and humidity distribution data, an electric field perpendicular to the membrane surface direction is applied to the hybrid solid electrolyte membrane, with an initial electric field strength of 0.5 kV / cm, and the liquid electrolyte is dripped onto the surface of the hybrid solid electrolyte membrane under the action of the electric field to obtain ion concentration distribution data and solvent diffusion data in the membrane; The electric field strength was adjusted according to the ion concentration distribution data and the solvent diffusion data. When the local ion concentration exceeded 1.2 mol / L, the electric field strength was reduced to 0.3 kV / cm. When the local ion concentration was lower than 0.8 mol / L, the electric field strength was increased to 0.7 kV / cm. The infiltration time was controlled to 30-45 minutes to obtain a uniformly infiltrated hybrid solid electrolyte membrane.
[0011] Optionally, the step of heat treating and stress regulating the uniformly infiltrated hybrid solid electrolyte membrane to obtain a structurally stable hybrid solid electrolyte membrane comprises: Obtain stress distribution data of the uniformly infiltrated hybrid solid electrolyte membrane, and when the local stress value is greater than 2MPa, set the heat treatment temperature of the corresponding area to 60-65°C, and when the local stress value is less than 2MPa, set the heat treatment temperature of the corresponding area to 50-55°C, and the heat treatment time is 4-6 hours to obtain a hybrid solid electrolyte membrane with thermal stress release; According to the ion conductivity distribution data of the hybrid solid electrolyte membrane with thermal stress release, selective microwave irradiation is performed on the area with ion conductivity lower than 0.5 mS / cm, the microwave frequency is controlled to be 2.45 GHz, the power density is 0.8-1.2 W / cm², and the irradiation time is 10-15 minutes to obtain a hybrid solid electrolyte membrane with ion channel activation; Under an inert atmosphere, based on the stress distribution data in the thickness direction of the ion channel-activated hybrid solid electrolyte membrane, a prestress field is applied to the ion channel-activated hybrid solid electrolyte membrane, the compressive stress parallel to the membrane surface is controlled to be 0.6-0.8MPa, and the tensile stress perpendicular to the membrane surface is controlled to be 0.3-0.4MPa. The prestress is maintained for 2-3 hours to obtain a structurally stable hybrid solid electrolyte membrane.
[0012] Optionally, a nano-interface layer is constructed on the surface of the self-supporting electrode, and the structurally stable hybrid solid electrolyte membrane is laminated with the self-supporting electrode to obtain a flexible solid-state battery pack, comprising: Under an inert atmosphere, lithium titanate is dissolved in isopropanol, polyvinylidene fluoride-hexafluoropropylene copolymer is added as a binder, the mass ratio of the lithium titanate to the polyvinylidene fluoride-hexafluoropropylene copolymer is controlled to be 4:1, after being stirred evenly, spin-coated on the surface of a self-supporting electrode, and dried at 80° C. for 2 hours to obtain a self-supporting electrode with a nano interface layer; The structurally stable hybrid solid electrolyte membrane is attached to the surface of the self-supporting electrode with the nano interface layer, and hot pressing is performed under an inert atmosphere by temperature-pressure coordinated control, wherein the hot pressing temperature is 70-80° C., the pressure is 2-3 MPa, and the holding time is 30-40 minutes to obtain a first electrode laminate structure; preparing a second self-supporting electrode having a nano interface layer, and laminating the second self-supporting electrode having a nano interface layer with the first electrode laminate structure using the same lamination process as the first electrode laminate structure to obtain an electrode-electrolyte-electrode laminate structure; A UV-curable epoxy resin sealing layer is coated on the peripheral area of the laminated structure, and ultraviolet light is irradiated in an inert atmosphere, the light intensity is controlled to be 80-100mW / cm², and the irradiation time is 5-8 minutes to obtain a flexible solid-state battery pack.
[0013] A second aspect of the present invention provides a solid-state battery pack, which is prepared by the processing method of the solid-state battery pack of the above embodiment.
[0014] The present invention provides a processing method for a flexible solid-state battery pack. First, by performing surface modification on the polymer matrix and the inorganic filler respectively, the problem of mismatched interfacial tension between the two can be effectively alleviated. The modified inorganic filler forms a more uniform and tight bonding interface in the polymer network, reducing the possibility of local repulsion or excessive swelling in subsequent infiltration. This step not only improves the affinity between the materials at the molecular level, but also lays the prerequisite for uniform dispersion for subsequent liquid electrolyte infiltration. If these interface modifications are not performed, the inorganic particles often cannot be fully wetted or locally agglomerated, resulting in problems such as discontinuous ion transport paths and difficulty in eliminating local voids during the subsequent infiltration process.
[0015] Next, the membrane is infiltrated using an electric field-assisted method, relying on real-time monitoring of the ion concentration and solvent diffusion data during the infiltration process to dynamically adjust the intensity and distribution of the electric field. This can maintain a relatively constant and controllable ion diffusion rate in different areas of the membrane, avoiding local over-expansion due to excessive absorption of solvent in some areas, and inhibiting insufficient infiltration in other areas due to rejection or rapid evaporation. Compared with passive infiltration methods, this targeted electric field control makes it easier for ions to be evenly distributed in the membrane, thereby significantly reducing the risks of microscopic gaps and late side reactions caused by uneven infiltration.
[0016] Subsequently, after obtaining a uniformly infiltrated membrane, heat treatment and stress control methods are used to further release or disperse the internal stress left over from the infiltration process and repair tiny defective areas. During the heat treatment stage, customized temperature management or local energy input is implemented for different areas according to the distribution of local stress and ion conductivity, which can effectively relax the polymer segments in places where stress is concentrated, while also promoting a more stable interface between the inorganic filler and the matrix. On this basis, the stress control strategy is used to redistribute or offset the residual stress that may be generated in a preset direction, which helps to prevent the expansion of any fine cracks and make the internal structure of the membrane more uniform and stable.
[0017] Finally, the treated membrane is laminated with a self-supporting electrode, and a nanoscale interface modification layer is constructed on the electrode surface to further enhance the contact quality between the electrode and the electrolyte membrane. Through the coordinated control of the three elements of pressure, temperature and time, the membrane and the electrode can form a dense and smooth bonding surface at the microscopic scale. In addition, the conductivity and mechanical buffering properties of the nano-interface modification layer not only improve the transmission efficiency of ions at the interface, but also prevent the interface stratification that may occur during multiple bending or thermal shock in the later stage. In this way, the entire processing process works together in multiple dimensions such as material modification, wetting adjustment, defect repair and lamination protection, which can reduce the potential hazards caused by the volatilization of trace moisture, oxygen or uneven solvents in an open environment from the source, and ensure that the hybrid solid electrolyte membrane maintains a stable mechanical structure and good ion transmission performance during large-scale manufacturing and subsequent applications, thereby successfully resolving the safety and life bottlenecks caused by uneven wetting and accumulation of microscopic defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0019] Figure 1 Schematic diagram of an embodiment of a method for processing a solid-state battery pack in an embodiment of the present invention.
[0020] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0023] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, which must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0024] An embodiment of the present application provides a method for processing a solid-state battery pack. Figure 1 A flow chart of a method for processing a solid-state battery pack provided in one embodiment of the present application. In this embodiment, the method includes: See also Figure 1 , performing surface modification treatment on the polymer matrix and the inorganic filler, dispersing the modified inorganic filler in the modified polymer matrix, and preparing a hybrid solid electrolyte membrane; In one embodiment of the present invention, the surface modification treatment of the polymer matrix and the inorganic filler comprises: Polyvinylidene fluoride-hexafluoropropylene copolymer is selected as the polymer matrix, and lithium lanthanum zirconium titanium oxide is selected as the inorganic filler; The surface of the lithium lanthanum zirconium titanium oxide is activated by oxygen plasma to adjust the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide, and then the surface of the lithium lanthanum zirconium titanium oxide is coordinated and modified by a silane coupling agent to obtain a surface-modified lithium lanthanum zirconium titanium oxide; The quaternary ammonium salt group is introduced into the molecular chain of the polyvinylidene fluoride-hexafluoropropylene copolymer by peroxide-initiated grafting, and then the polyvinylidene fluoride-hexafluoropropylene copolymer is selectively fluorinated to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
[0025] The following is a specific description of the steps involved in the above embodiment. In the first step, the raw materials in the form of polyvinylidene fluoride-hexafluoropropylene copolymer particles or powders and lithium lanthanum zirconium titanium oxide can be preliminarily screened and graded. The former exhibits heat resistance and strong chemical stability characteristics due to the presence of fluorine in the molecular structure, and can still maintain a certain mechanical strength under flexible conditions; the latter is used as a ceramic material with good ion conductivity and is used to strengthen the transmission channel. In order to facilitate subsequent operations, the lithium lanthanum zirconium titanium oxide can be adjusted to a more uniform particle size distribution using a grinding device or a ball milling device (such as a small planetary ball mill) to ensure the effectiveness of subsequent surface treatment. In this selection step, if it is necessary to change the type of ions or improve the durability of the membrane, other fluorine-based polymer systems can be used or lithium lanthanum zirconium titanium oxide can be replaced with materials with the same crystal form but slightly different doping components. Through this step, a mutually matching polymer matrix and inorganic skeleton are obtained, which provides a suitable material combination for the interface stability and ion transmission rate in the subsequent processing links.
[0026] In the second step, the lithium lanthanum zirconium titanium oxide can be pre-dispersed in anhydrous ethanol or other low-polarity solvents, stirred or ultrasonically dispersed for a short time in an inert environment (such as nitrogen), and then placed in a vacuum drying environment to remove solvent residues. The treated powder is sent to a plasma device, and the oxygen flow and plasma energy are used to clean the organic residues on the surface of the particles and activate the lithium ion state of the surface. At this time, the exposure degree of lithium ions on the surface and the distribution of oxidation states can be further affected by adjusting the oxygen flow and radio frequency power. Subsequently, the surface-activated powder is mixed with a silane coupling agent (such as γ-glycidyloxypropyltrimethoxysilane) solution and reacted under stirring or constant temperature conditions. The silane molecules will coordinate or chemically bond with the active sites on the surface of the particles, thereby forming a modified layer around the particles that is both organic-philic and inorganic-philic. If the degree of compatibility between the particles and the polymer interface needs to be changed in this process, other types of coupling agents can be used instead. Through this operation, the obtained lithium lanthanum zirconium titanium oxide exhibits good dispersibility and can be more closely combined with the subsequent polymer matrix.
[0027] In the third step, the polyvinylidene fluoride-hexafluoropropylene copolymer can be dissolved in an appropriate solvent (such as tetrahydrofuran), and benzoyl peroxide or similar peroxides can be added as a free radical initiator to provide a free radical source for the subsequent grafting reaction. When the monomer or prepolymer corresponding to the quaternary ammonium salt group is mixed with the solution, a free radical reaction can occur under moderate temperature conditions, so that the quaternary ammonium salt group is stably grafted onto the polymer backbone. Subsequently, the grafted polymer can be sent to a selective fluorination system after removing residual solvents or by-products, so that the fluorinated gas has a gradient penetration effect on the surface within a limited layer thickness range, so that the membrane surface has a higher polar area, while the interior still maintains the original non-polar characteristics. If you want to increase the surface polarity range, you can appropriately extend the fluorine gas residence time or increase the fluorine gas concentration. After this fluorination process, the material obtains different interfacial energy distributions between the surface and the interior, which is conducive to the close binding of inorganic particles and the improvement of ion transmission capacity.
[0028] After completing the above three treatments, the modified inorganic filler and modified polymer can more evenly penetrate or bond with each other, and maintain a stable ion diffusion path and structural stability under electrochemical environment. This material system not only shows considerable mechanical flexibility under normal temperature conditions, but also takes into account high reliability in terms of ion transmission and interface stability.
[0029] In one embodiment of the present invention, the peroxide-initiated grafting is used to introduce quaternary ammonium salt groups into the molecular chains of the polyvinylidene fluoride-hexafluoropropylene copolymer, and then the polyvinylidene fluoride-hexafluoropropylene copolymer is selectively fluorinated to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer, comprising: The polyvinylidene fluoride-hexafluoropropylene copolymer is dissolved in tetrahydrofuran, benzoyl peroxide is added as an initiator, and γ-methacryloxypropyltrimethoxysilane is added as an interface coupling agent, and the mixture is stirred and reacted at 60-70° C. for 2-3 hours to obtain a prepolymer having active sites; Adding dimethacryloyloxyethyl dodecyldimethyl quaternary ammonium salt monomer to the prepolymer having active sites, controlling the mass ratio of the quaternary ammonium salt monomer to the polyvinylidene fluoride-hexafluoropropylene copolymer to be 1:4 to 1:3, reacting at 75-85° C. for 4-6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer grafted with a quaternary ammonium salt group; The quaternary ammonium salt group-grafted polyvinylidene fluoride-hexafluoropropylene copolymer solution is cooled to 25-35° C., and a selective fluorination treatment is performed in a fluorine gas atmosphere with a controllable concentration gradient, wherein the fluorine gas volume fraction is distributed in a gradient of 20%:10%:5% from the surface layer to the inner layer, and the fluorination time is controlled to be 30-45 minutes to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
[0030] The following is a specific description of the steps involved in the above embodiment. In the first step, the polyvinylidene fluoride-hexafluoropropylene copolymer is dissolved in tetrahydrofuran, and a water bath or oil bath thermostat can be used to maintain the reaction system at a temperature range of 60-70°C. At this time, benzoyl peroxide needs to be added to the solution to provide a free radical source, and γ-methacryloxypropyltrimethoxysilane is introduced as an interfacial coupling agent. Benzoyl peroxide can decompose and generate free radicals under a heating environment, interact with the polyvinylidene fluoride-hexafluoropropylene copolymer molecular chain, and generate active sites. γ-methacryloxypropyltrimethoxysilane combines with these active sites under free radical conditions, so that some silane molecules are embedded or connected to the macromolecular chain, thereby giving the subsequent grafting reaction a higher bonding efficiency. A magnetic stirrer or an overhead stirrer can be used to keep uniform mixing during stirring, and a stable temperature and stirring speed can be maintained within 2-3 hours. After completing this stage, a prepolymer carrying a variety of reactive active groups can be obtained. If there are other requirements for the type of silane, it can also be replaced by other silane derivatives, but it must be ensured that it has sufficient reactivity under the same temperature and free radical environment.
[0031] In the second step, when adding dimethacryloyloxyethyl dodecyl dimethyl quaternary ammonium salt monomer to the above prepolymer with active sites, stirring should be continued for 4-6 hours in an environment of 75-85°C. Here, similar stirring and heating equipment as in the previous stage can be used to ensure that the temperature is relatively stable. Under the action of free radicals generated by the initiator, the dimethacryloyloxyethyl dodecyl dimethyl quaternary ammonium salt monomer undergoes a grafting reaction with the active sites on the molecular chain of the polyvinylidene fluoride-hexafluoropropylene copolymer, so that the quaternary ammonium salt structure is stably embedded in the polymer main chain or side chain. The ratio range of 1:4 to 1:3 by mass ratio can maintain a balance between the ionic conductivity characteristics and the mechanical stability of the polymer itself. If it is necessary to adjust the surface positive charge density or change the chain length of the quaternary ammonium salt monomer, other amine derivatives can also be selected for grafting. After the reaction is completed, the polymer macromolecular chain has a quaternary ammonium salt group, showing more significant ionic characteristics and improved interface binding potential.
[0032] In the third step, after the quaternary ammonium salt group-grafted polyvinylidene fluoride-hexafluoropropylene copolymer solution is gradually cooled to 25-35°C, a gradient-controlled fluorine gas atmosphere can be used for selective fluorination. In order to achieve different concentrations of fluorination levels from the surface to the inside, the fluorine gas volume fraction needs to be transported in three stages of 20%: 10%: 5% in sequence, and the entire treatment process lasts 30-45 minutes. The low temperature environment and staged fluorine gas input can enable fluorine atoms to form a higher fluorine-containing area on the polymer surface, while the fluorination degree of the area close to the inside is relatively low, thereby obtaining a polarity gradient characteristic. This operation can be performed in a closed reaction vessel using common fluorination process equipment, and the fluorination time can be set according to the film thickness and fluorine gas concentration. If the polarity requirements of the material change, the fluorine gas concentration or delivery time can also be adjusted. After completing this selective fluorination, the resulting polyvinylidene fluoride-hexafluoropropylene copolymer presents a differentiated surface energy distribution between the surface and the inside, which is conducive to the later combination with inorganic fillers or other material layers, and can maintain the overall mechanical and electrochemical stability properties.
[0033] In one embodiment of the present invention, the surface activation of the lithium lanthanum zirconium titanium oxide is performed by oxygen plasma, the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide is regulated, and then the surface coordination modification of the lithium lanthanum zirconium titanium oxide is performed by a silane coupling agent to obtain a surface-modified lithium lanthanum zirconium titanium oxide, comprising: The lithium lanthanum zirconium titanium oxide is dispersed in anhydrous ethanol, pretreated for 2-3 hours under an inert atmosphere, and then treated with oxygen plasma at a power of 50W-100W, with the oxygen flow rate controlled to be 20-30sccm for a treatment time of 15-30 minutes, and the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide is regulated by adjusting the ratio of plasma power to oxygen flow rate, and then dried under a vacuum environment for 4-6 hours to obtain a surface-activated lithium lanthanum zirconium titanium oxide; Under an inert atmosphere, a γ-glycidyloxypropyltrimethoxysilane coupling agent is dissolved in anhydrous tetrahydrofuran, and the surface-activated lithium lanthanum zirconium titanium oxide is added, and the mass ratio of the coupling agent to the lithium lanthanum zirconium titanium oxide is controlled to be 1:10 to 1:8. The reaction is stirred at 40-50° C. for 2-3 hours, and the mixture is centrifugally washed with anhydrous ethanol for 3-4 times and then vacuum dried at 60-70° C. for 8-12 hours to obtain a surface-modified lithium lanthanum zirconium titanium oxide.
[0034] The following is a specific description of the steps involved in the above embodiment. In the first step, when the lithium lanthanum zirconium titanium oxide is placed in anhydrous ethanol for dispersion treatment, it can be stirred continuously for 2-3 hours under an inert atmosphere (such as nitrogen, the inert atmosphere conditions in the embodiments below can all be nitrogen atmosphere conditions, and will not be repeated later) to reduce the interference of the oxygen content and moisture content in the environment on the dispersion effect. After the initial dispersion is completed, the dispersion is filtered or centrifuged to obtain a sample in a particle state, and then placed in an oxygen plasma treatment system. By adjusting the power between 50W-100W, the oxygen flow rate within the range of 20-30sccm, and controlling the treatment time within 15-30 minutes, the distribution of active groups on the surface is changed. In this step, the ratio of plasma power to oxygen flow directly affects the redox state and exposure degree of lithium ions on the surface of the particles. Different power and flow combinations can produce different degrees of surface cleaning and oxidation, thereby controlling the surface lithium ion concentration. After the plasma treatment is completed, the particles can be sent to a vacuum drying oven to maintain a constant temperature and low pressure environment for 4-6 hours to fully volatilize and remove excess surface functional groups or adsorbents. In this stage, through atmosphere control and energy input, the surface of lithium lanthanum zirconium titanium oxide forms active sites suitable for subsequent reactions and obtains a purer surface state.
[0035] In the second step, in an inert atmosphere, the γ-glycidyloxypropyltrimethoxysilane coupling agent is dissolved in anhydrous tetrahydrofuran, and then the lithium lanthanum zirconium titanium oxide treated in the previous step is introduced, the mass ratio of the coupling agent to the lithium lanthanum zirconium titanium oxide is maintained between 1:10 and 1:8, and the reaction is stirred at 40-50°C for 2-3 hours. Within this temperature range, the coupling agent molecules can form a stable organic-inorganic bonding interface on the surface of the particles through hydrolysis and condensation reactions. After stirring, the particles are washed 3-4 times by centrifugation with anhydrous ethanol to remove possible residual solvents and unreacted products, and finally dried in a vacuum environment at 60-70°C for 8-12 hours to obtain surface-modified lithium lanthanum zirconium titanium oxide. This treatment method can establish a more compatible molecular layer on the surface of the particles, which not only maintains the original ionic conductivity characteristics of the material, but also makes it exhibit a more stable dispersion and bonding effect when combined with an organic matrix in the subsequent process. If there are more requirements for the degree of modification or the type of coupling agent, the type or concentration of the coupling agent can also be adjusted according to actual conditions to achieve a wider range of molecular modifications and surface functionalization.
[0036] In one embodiment of the present invention, the modified inorganic filler is dispersed in the modified polymer matrix to prepare a hybrid solid electrolyte membrane, comprising: Dispersing the surface-modified lithium lanthanum zirconium titanium oxide in N-methylpyrrolidone, adding ferrocene as a dispersion stabilizer to the obtained basic dispersion, controlling the mass ratio of ferrocene to the surface-modified lithium lanthanum zirconium titanium oxide to be 1:50 to 1:30, and dispersing under ultrasonic conditions for 2-3 hours to obtain a first dispersion; Dissolving the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer in the first dispersion, controlling the mass fraction of the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer to be 15wt%-20wt%, and stirring uniformly at 60-70°C for 4-6 hours to obtain a uniform dispersion; The uniform dispersion is coated with an automatic coating machine at a coating speed of 2-4 mm / s and the substrate temperature is controlled at 40-50°C to obtain a wet film, which is then transferred to a vacuum oven and dried at 50°C for 4-6 hours and then at 80°C for 8-12 hours to obtain a hybrid solid electrolyte membrane.
[0037] The following is a specific description of the steps involved in the above embodiment. In the first step, the surface-modified lithium lanthanum zirconium titanium oxide is put into an N-methylpyrrolidone solvent, and after it is initially dispersed by stirring or a small amount of pre-grinding means, ferrocene is added to stabilize the dispersed state. Ferrocene can form a strong interaction with the particle surface in this environment, reduce agglomeration and maintain the stability of the dispersion. Controlling the mass ratio in the range of 1:50 to 1:30 can avoid excessive dispersant causing viscosity increase, and can also keep the solid particles separated in the solvent. Subsequently, it is treated within 2-3 hours with the help of an ultrasonic device to make the inorganic particles more evenly distributed in the liquid phase to form a first dispersion compatible with an organic matrix. If you want to change the type of dispersant, ferrocene can be replaced with other organic molecules or metal organic compounds with good compatibility, but it is necessary to ensure that the particle surface has sufficient adsorption capacity.
[0038] In the second step, the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer is introduced into the first dispersion to keep the two mixed as evenly as possible at the molecular level. This method requires stirring after the polymer is dissolved, setting the temperature in the range of 60-70°C, and maintaining a stable stirring speed for 4-6 hours. This allows the grafted polymer to fully dissolve and form a good interaction with the first dispersion. The mass fraction is kept in the range of 15wt%-20%, which can not only improve the mechanical support of the final membrane, but also maintain fluidity and wettability. If this value must be adjusted, the solvent type can be replaced or the mixing ratio of the polymer and the dispersion can be changed according to the desired film toughness and inorganic loading requirements. After this stage, a mixed solution with suitable viscosity and uniform dispersion is obtained, which provides a stable basic system for the subsequent film-forming steps.
[0039] In the third step, when the above-mentioned mixed liquid is coated with an automatic coating machine, the coating speed should be in the range of 2-4mm / s so that the liquid forms a flat wet film on the surface of the substrate. A constant temperature coating platform can be used to keep the substrate at 40-50°C, so that the solvent can evaporate moderately and the probability of film surface defects can be reduced. After the wet film is formed, it is transferred to a vacuum oven and dried at 50°C for 4-6 hours to remove most of the solvent; then it is continued to dry at 80°C for 8-12 hours to enhance the structural density and firmness of the membrane. This graded drying process can avoid uneven shrinkage caused by sudden temperature changes, and make the inorganic particles closely combined with the polymer matrix. The resulting hybrid solid electrolyte membrane can meet the predetermined requirements in terms of ion transport and mechanical toughness. If the production scale is large or there are more requirements for film thickness accuracy, a multi-stage heating program can be used in this step or a continuous roller drying system can be used instead.
[0040] Please continue reading Figure 1 , infiltrating the hybrid solid electrolyte membrane with liquid electrolyte under the action of an electric field, adjusting the electric field parameters according to the ion concentration distribution and solvent diffusion data during the infiltration process, to obtain a uniformly infiltrated hybrid solid electrolyte membrane; In one embodiment of the present invention, the hybrid solid electrolyte membrane is infiltrated with a liquid electrolyte under the action of an electric field, and the electric field parameters are adjusted according to the ion concentration distribution and solvent diffusion data during the infiltration process to obtain a uniformly infiltrated hybrid solid electrolyte membrane, including: dissolving lithium trifluoromethanesulfonyl diimide in a mixed solvent of ethylene carbonate and dimethyl carbonate, controlling the volume ratio of the ethylene carbonate to the dimethyl carbonate to be 1:1, and controlling the concentration of the lithium trifluoromethanesulfonyl diimide to be 1 mol / L, to obtain a liquid electrolyte; Under an environment of 35° C. and a relative humidity of 40%, a temperature and humidity gradient field is constructed around the hybrid solid electrolyte membrane, so that the temperature is distributed in a gradient from 35° C. to 25° C. from the inside to the outside, and the relative humidity is distributed in a gradient from 40% to 20% from the inside to the outside, and the temperature and humidity distribution data on the surface of the hybrid solid electrolyte membrane are obtained; According to the temperature and humidity distribution data, an electric field perpendicular to the membrane surface direction is applied to the hybrid solid electrolyte membrane, with an initial electric field strength of 0.5 kV / cm, and the liquid electrolyte is dripped onto the surface of the hybrid solid electrolyte membrane under the action of the electric field to obtain ion concentration distribution data and solvent diffusion data in the membrane; The electric field strength was adjusted according to the ion concentration distribution data and the solvent diffusion data. When the local ion concentration exceeded 1.2 mol / L, the electric field strength was reduced to 0.3 kV / cm. When the local ion concentration was lower than 0.8 mol / L, the electric field strength was increased to 0.7 kV / cm. The infiltration time was controlled to 30-45 minutes to obtain a uniformly infiltrated hybrid solid electrolyte membrane.
[0041] The steps involved in the above-mentioned embodiment are specifically described below. In the first step, the trifluoromethanesulfonyl diimide lithium is first mixed with an equal volume of ethylene carbonate and dimethyl carbonate by accurate weighing and liquid preparation. A stirring device can be used to maintain the stability of the solution in an inert atmosphere or a low humidity environment. At this time, the addition amount of the trifluoromethanesulfonyl diimide lithium needs to be accurately calculated according to the required concentration and configured within the range of 1 mol / L. This step generally does not require a heating operation, and a liquid electrolyte that meets the expected ionic conductive characteristics can be obtained at room temperature. If you want to obtain different ionic conductive properties, you can also replace ethylene carbonate with other solvents such as propylene carbonate, but it is necessary to ensure that it maintains a chemically stable relationship with the trifluoromethanesulfonyl diimide lithium.
[0042] In the second step, a multi-zone control method is then used to form a temperature and humidity gradient condition around the site at 35°C and a relative humidity of 40%, so that the area close to the hybrid solid electrolyte membrane maintains a higher temperature and humidity, and the area away from the membrane presents a slightly lower temperature and humidity. In order to achieve a stable gradient change, a multi-channel temperature and humidity controller can be used and temperature and humidity sensors can be placed at different distances to read the values in real time. This approach can grasp the temperature and humidity difference between the membrane surface and the external environment, thereby forming a gradually decreasing temperature and humidity distribution around the membrane. The regulation of such parameters can also be combined with local air supply or directional partitions for zoning. If there are different considerations for production efficiency, a finer gradient difference can be set to match the characteristics of the membrane material.
[0043] In the third step, after monitoring the target temperature and humidity gradient, an electric field perpendicular to the membrane surface is applied to the membrane, and the electrolyte solution is dispersed to the membrane surface through a dropper or a micro-injection pump with a starting intensity of 0.5 kV / cm. In this process, the ion concentration distribution data inside the membrane can be collected using an ion concentration sensor or a surface impedance detection device, and the solvent diffusion status can be collected with the help of an infrared or mass monitor. If the monitoring equipment equipped on site is more advanced, in-situ optical observations can also be implemented to evaluate the dynamic wetting process of the membrane pores. In this link, an external electric field is used to promote the synchronous migration of charged ions and polar solvents, so that the surface and internal infiltration progress remain relatively consistent.
[0044] In the fourth step, the electric field strength is dynamically adjusted to a more suitable range according to the ion concentration and solvent diffusion information obtained from the monitoring equipment. When the local ion concentration data shows that the concentration value is higher than 1.2mol / L, the electric field strength is reduced to 0.3kV / cm to reduce the excessive aggregation phenomenon; when the local ion concentration is lower than 0.8mol / L, the electric field strength is increased to 0.7kV / cm to enhance the infiltration and migration rate in the membrane. The entire infiltration operation generally lasts 30-45 minutes to ensure that the distribution of liquid electrolyte in various regions of the membrane is in a balanced state. This type of infiltration method that adjusts the electric field at any time helps to form a solid electrolyte membrane with uniform ion concentration and achieve the expected conductive function and structural consistency.
[0045] Please continue reading Figure 1 , heat treating and stress regulating the uniformly infiltrated hybrid solid electrolyte membrane to obtain a hybrid solid electrolyte membrane with a stable structure; In one embodiment of the present invention, the heat treatment and stress regulation of the uniformly infiltrated hybrid solid electrolyte membrane to obtain a structurally stable hybrid solid electrolyte membrane comprises: Obtain stress distribution data of the uniformly infiltrated hybrid solid electrolyte membrane, and when the local stress value is greater than 2MPa, set the heat treatment temperature of the corresponding area to 60-65°C, and when the local stress value is less than 2MPa, set the heat treatment temperature of the corresponding area to 50-55°C, and the heat treatment time is 4-6 hours to obtain a hybrid solid electrolyte membrane with thermal stress release; According to the ion conductivity distribution data of the hybrid solid electrolyte membrane with thermal stress release, selective microwave irradiation is performed on the area with ion conductivity lower than 0.5 mS / cm, the microwave frequency is controlled to be 2.45 GHz, the power density is 0.8-1.2 W / cm², and the irradiation time is 10-15 minutes to obtain a hybrid solid electrolyte membrane with ion channel activation; Under an inert atmosphere, based on the stress distribution data in the thickness direction of the ion channel-activated hybrid solid electrolyte membrane, a prestress field is applied to the ion channel-activated hybrid solid electrolyte membrane, the compressive stress parallel to the membrane surface is controlled to be 0.6-0.8MPa, and the tensile stress perpendicular to the membrane surface is controlled to be 0.3-0.4MPa. The prestress is maintained for 2-3 hours to obtain a structurally stable hybrid solid electrolyte membrane.
[0046] The following is a specific description of the steps involved in the above embodiment. In the first step, a stress detection system such as a digital image correlator or a laser speckle interferometer can be used to perform multi-point scanning on the electrolyte membrane that has been uniformly infiltrated to obtain stress information at different positions. If it is found that the stress value of the local area exceeds 2MPa, this part can be maintained in the range of 60-65°C through a partitioned temperature control platform; if the stress value is below 2MPa, 50-55°C is used for heating. Differentiating the treatment temperature can ensure that the high stress area is fully strain-released and avoid excessive thermal stimulation to the low stress area. After setting the continuous heating for 4-6 hours, the relaxation phenomenon at the interface between the molecular chain segment and the inorganic filler will be more fully exerted, thereby reducing the strain accumulation inside the material. For large-scale membrane processing, a layered heating cabinet or a multi-channel temperature control device can also be combined to achieve synchronous differentiated adjustment of multiple batches.
[0047] In the second step, after the heat treatment, the ion conductivity level can be determined by an AC impedance meter or a surface scanning conductivity tester, and the area with low conductivity values (less than 0.5mS / cm) can be selected for subsequent microwave activation. In order to concentrate the microwave energy only on the required part, a 2.45GHz microwave generator with focusing function can be used, combined with an integrated waveguide to control the power density to 0.8-1.2W / cm². The irradiation time is kept at 10-15 minutes, so that the polymer molecules will locally heat up under the action of microwaves and enhance the flexibility of the chain segments. This will further open the ion channels without the need for uniform heating of the entire membrane. If the on-site equipment or materials permit, infrared scanning heads or visible light local heating solutions can also be used to enhance the conduction characteristics in small areas. After this process, the ion diffusion channels of the membrane will tend to be spatially balanced, thereby improving the overall electrochemical performance.
[0048] In the third step, in an inert environment, the membrane with activated ion channels is placed in an adjustable multi-directional stress fixture, and precise pressure and tension are applied in different directions according to the measured stress distribution in the membrane thickness direction. A compressive stress of 0.6-0.8MPa is maintained in the direction parallel to the membrane surface, and a tensile stress of 0.3-0.4MPa is applied in the direction perpendicular to the membrane surface, and the pressure is maintained for 2-3 hours. This solution can stably shape the membrane layer under a multi-axial stress environment to avoid interface cracking or internal defect expansion due to uneven strain during subsequent use. During the implementation process, high-precision pressure sensors and load control systems can be used to dynamically adjust the stress values in two directions. After completing this step, the electrolyte membrane reaches a state of equilibrium in both mechanical and electrochemical aspects, which is suitable for subsequent flexible battery assembly or other high-reliability applications.
[0049] Please continue reading Figure 1 , constructing a nano-interface layer on the surface of the self-supporting electrode, laminating the structurally stable hybrid solid electrolyte membrane with the self-supporting electrode to obtain a flexible solid-state battery pack.
[0050] In one embodiment of the present invention, the nano-interface layer is constructed on the surface of the self-supporting electrode, and the structurally stable hybrid solid electrolyte membrane is laminated with the self-supporting electrode to obtain a flexible solid-state battery pack, comprising: Under an inert atmosphere, lithium titanate is dissolved in isopropanol, polyvinylidene fluoride-hexafluoropropylene copolymer is added as a binder, the mass ratio of the lithium titanate to the polyvinylidene fluoride-hexafluoropropylene copolymer is controlled to be 4:1, after being stirred evenly, spin-coated on the surface of a self-supporting electrode, and dried at 80° C. for 2 hours to obtain a self-supporting electrode with a nano interface layer; The structurally stable hybrid solid electrolyte membrane is attached to the surface of the self-supporting electrode with the nano interface layer, and hot pressing is performed under an inert atmosphere by temperature-pressure coordinated control, wherein the hot pressing temperature is 70-80° C., the pressure is 2-3 MPa, and the holding time is 30-40 minutes to obtain a first electrode laminate structure; preparing a second self-supporting electrode having a nano interface layer, and laminating the second self-supporting electrode having a nano interface layer with the first electrode laminate structure using the same lamination process as the first electrode laminate structure to obtain an electrode-electrolyte-electrode laminate structure; A UV-curable epoxy resin sealing layer is coated on the peripheral area of the laminated structure, and ultraviolet light is irradiated in an inert atmosphere, the light intensity is controlled to be 80-100mW / cm², and the irradiation time is 5-8 minutes to obtain a flexible solid-state battery pack.
[0051] The following is a specific description of the steps involved in the above embodiment. In the first step, lithium titanate can be dissolved in an isopropanol medium under an inert environment, and polyvinylidene fluoride-hexafluoropropylene copolymer is added as a matching bonding component to keep lithium titanate suspended and stable in the solvent. In order to achieve better viscosity and uniformity, the mass ratio of the two needs to be controlled at 4:1, and a stirrer is used to mix at room temperature or slightly higher temperature. The resulting slurry can be applied to the surface of the self-supporting electrode by a spin coater, and the spin coating speed and time should be set according to the target film thickness. Subsequently, the coated substrate is placed at about 80°C and dried for 2 hours to fully volatilize the solvent and form a nano-scale adhesion layer with lithium titanate and polyvinylidene fluoride-hexafluoropropylene copolymer. If there are other requirements for film uniformity or conductivity, direct spraying or scraping process can also be used instead, but a low air flow rate should be maintained to avoid excessive scattering of active particles.
[0052] In the second step, the obtained hybrid solid electrolyte membrane is bonded to the electrode surface with an adhesion layer, and placed in an inert atmosphere environment for hot pressing using a temperature and pressure coordinated adjustment mode. The specific operation can use a pressing device that can monitor and control temperature (70-80°C) and pressure (2-3MPa), and maintain a holding time of about 30-40 minutes. By applying force in segments and monitoring the fit of the membrane surface, close contact between the electrode and the electrolyte can be achieved at the microscopic level, and the interface air gap can be reduced. For large-area battery cells, multi-point temperature and pressure sensors can be configured to adjust local parameters in time to obtain consistent lamination quality. The final structure is in a state of balance in terms of mechanical strength and ion transport.
[0053] In the third step, for the single-sided structure after the above-mentioned electrode lamination, the same process can be used to make the other side of the nano-interface layer electrode, and combined with the structure of the first side with the electrolyte to form a multi-layer stack. This operation also requires strict alignment of the second electrode and the electrolyte membrane, and then the lamination is completed by the same set of temperature and pressure control methods. When used in batch production lines, it is possible to consider connecting multiple hot pressing devices in parallel or using an assembly line stacking system. The stacking system thus formed exhibits a more complete electrochemical function between the conductive end and the electrolyte end, and can be directly used as the main component for subsequent packaging and testing.
[0054] In the fourth step, a UV-curable epoxy formula can be used to seal the seams or exposed edges in the outer edge area of the obtained multilayer structure. The formula can be evenly covered on the periphery through dispensing or spraying equipment, and the UV light source provides an irradiation intensity of about 80-100mW / cm² for 5-8 minutes to achieve rapid curing of the epoxy resin. An inert atmosphere needs to be maintained during the sealing process to prevent moisture or oxygen molecules in the air from invading and causing defects in the bonding layer. The resulting overall component can maintain safe operation under high flexibility conditions and maintain electrochemical stability over a long working cycle. If the packaging morphology changes according to different terminal applications, other resin materials that can be quickly cross-linked or prefabricated sealing film solutions can also be used.
[0055] Another embodiment of the present application further provides a solid-state battery pack prepared using any of the above embodiments.
[0056] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for processing a solid-state battery pack, characterized in that: include: The polymer matrix and the inorganic filler are subjected to surface modification treatment, and the modified inorganic filler is dispersed in the modified polymer matrix to prepare a hybrid solid electrolyte membrane; Infiltrating the hybrid solid electrolyte membrane with liquid electrolyte under the action of an electric field, adjusting electric field parameters according to ion concentration distribution and solvent diffusion data during the infiltration process, to obtain a uniformly infiltrated hybrid solid electrolyte membrane; Performing heat treatment and stress control on the uniformly infiltrated hybrid solid electrolyte membrane to obtain a hybrid solid electrolyte membrane with a stable structure; A nano interface layer is constructed on the surface of the self-supporting electrode, and the structurally stable hybrid solid electrolyte membrane is laminated with the self-supporting electrode to obtain a flexible solid-state battery pack.
2. The method for processing a solid-state battery pack according to claim 1, characterized in that: The surface modification treatment of the polymer matrix and the inorganic filler comprises: Polyvinylidene fluoride-hexafluoropropylene copolymer is selected as the polymer matrix, and lithium lanthanum zirconium titanium oxide is selected as the inorganic filler; The surface of the lithium lanthanum zirconium titanium oxide is activated by oxygen plasma to adjust the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide, and then the surface of the lithium lanthanum zirconium titanium oxide is coordinated and modified by a silane coupling agent to obtain a surface-modified lithium lanthanum zirconium titanium oxide; The quaternary ammonium salt group is introduced into the molecular chain of the polyvinylidene fluoride-hexafluoropropylene copolymer by peroxide-initiated grafting, and then the polyvinylidene fluoride-hexafluoropropylene copolymer is selectively fluorinated to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
3. The processing method of the solid-state battery pack according to claim 2, characterized in that: The method comprises introducing quaternary ammonium salt groups into the molecular chains of the polyvinylidene fluoride-hexafluoropropylene copolymer by peroxide-initiated grafting, and then selectively fluorinating the polyvinylidene fluoride-hexafluoropropylene copolymer to form a polarity gradient distribution on the surface of the polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer, comprising: The polyvinylidene fluoride-hexafluoropropylene copolymer is dissolved in tetrahydrofuran, benzoyl peroxide is added as an initiator, and γ-methacryloxypropyltrimethoxysilane is added as an interface coupling agent, and the mixture is stirred and reacted at 60-70° C. for 2-3 hours to obtain a prepolymer having active sites; Adding dimethacryloyloxyethyl dodecyldimethyl quaternary ammonium salt monomer to the prepolymer having active sites, controlling the mass ratio of the quaternary ammonium salt monomer to the polyvinylidene fluoride-hexafluoropropylene copolymer to be 1:4 to 1:3, reacting at 75-85° C. for 4-6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer grafted with a quaternary ammonium salt group; The quaternary ammonium salt group-grafted polyvinylidene fluoride-hexafluoropropylene copolymer solution is cooled to 25-35° C., and a selective fluorination treatment is performed in a fluorine gas atmosphere with a controllable concentration gradient, wherein the fluorine gas volume fraction is distributed in a gradient of 20%:10%:5% from the surface layer to the inner layer, and the fluorination time is controlled to be 30-45 minutes to obtain a surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer.
4. The method for processing a solid-state battery pack according to claim 2, characterized in that: The method comprises: using oxygen plasma to activate the surface of the lithium lanthanum zirconium titanium oxide, regulating the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide, and then using a silane coupling agent to perform surface coordination modification on the lithium lanthanum zirconium titanium oxide to obtain a surface-modified lithium lanthanum zirconium titanium oxide, comprising: The lithium lanthanum zirconium titanium oxide is dispersed in anhydrous ethanol, pretreated for 2-3 hours under an inert atmosphere, and then treated with oxygen plasma at a power of 50W-100W, with the oxygen flow rate controlled to be 20-30sccm for a treatment time of 15-30 minutes, and the lithium ion concentration on the surface of the lithium lanthanum zirconium titanium oxide is regulated by adjusting the ratio of plasma power to oxygen flow rate, and then dried under a vacuum environment for 4-6 hours to obtain a surface-activated lithium lanthanum zirconium titanium oxide; Under an inert atmosphere, a γ-glycidyloxypropyltrimethoxysilane coupling agent is dissolved in anhydrous tetrahydrofuran, and the surface-activated lithium lanthanum zirconium titanium oxide is added, and the mass ratio of the coupling agent to the lithium lanthanum zirconium titanium oxide is controlled to be 1:10 to 1:
8. The reaction is stirred at 40-50° C. for 2-3 hours, and the mixture is centrifugally washed with anhydrous ethanol for 3-4 times and then vacuum dried at 60-70° C. for 8-12 hours to obtain a surface-modified lithium lanthanum zirconium titanium oxide.
5. The method for processing a solid-state battery pack according to claim 2, characterized in that: The modified inorganic filler is dispersed in the modified polymer matrix to prepare a hybrid solid electrolyte membrane, comprising: Dispersing the surface-modified lithium lanthanum zirconium titanium oxide in N-methylpyrrolidone, adding ferrocene as a dispersion stabilizer to the obtained basic dispersion, controlling the mass ratio of ferrocene to the surface-modified lithium lanthanum zirconium titanium oxide to be 1:50 to 1:30, and dispersing under ultrasonic conditions for 2-3 hours to obtain a first dispersion; Dissolving the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer in the first dispersion, controlling the mass fraction of the surface-modified polyvinylidene fluoride-hexafluoropropylene copolymer to be 15wt%-20wt%, and stirring uniformly at 60-70°C for 4-6 hours to obtain a uniform dispersion; The uniform dispersion is coated with an automatic coating machine at a coating speed of 2-4 mm / s and the substrate temperature is controlled at 40-50°C to obtain a wet film, which is then transferred to a vacuum oven and dried at 50°C for 4-6 hours and then at 80°C for 8-12 hours to obtain a hybrid solid electrolyte membrane.
6. The method for processing a solid-state battery pack according to claim 1, characterized in that: The method of infiltrating the hybrid solid electrolyte membrane with liquid electrolyte under the action of an electric field, adjusting the electric field parameters according to the ion concentration distribution and solvent diffusion data during the infiltration process, and obtaining a uniformly infiltrated hybrid solid electrolyte membrane comprises: dissolving lithium trifluoromethanesulfonyl diimide in a mixed solvent of ethylene carbonate and dimethyl carbonate, controlling the volume ratio of the ethylene carbonate to the dimethyl carbonate to be 1:1, and controlling the concentration of the lithium trifluoromethanesulfonyl diimide to be 1 mol / L, to obtain a liquid electrolyte; Under an environment of 35° C. and a relative humidity of 40%, a temperature and humidity gradient field is constructed around the hybrid solid electrolyte membrane, so that the temperature is distributed in a gradient from 35° C. to 25° C. from the inside to the outside, and the relative humidity is distributed in a gradient from 40% to 20% from the inside to the outside, and the temperature and humidity distribution data on the surface of the hybrid solid electrolyte membrane are obtained; According to the temperature and humidity distribution data, an electric field perpendicular to the membrane surface direction is applied to the hybrid solid electrolyte membrane, with an initial electric field strength of 0.5 kV / cm, and the liquid electrolyte is dripped onto the surface of the hybrid solid electrolyte membrane under the action of the electric field to obtain ion concentration distribution data and solvent diffusion data in the membrane; The electric field strength was adjusted according to the ion concentration distribution data and the solvent diffusion data. When the local ion concentration exceeded 1.2 mol / L, the electric field strength was reduced to 0.3 kV / cm. When the local ion concentration was lower than 0.8 mol / L, the electric field strength was increased to 0.7 kV / cm. The infiltration time was controlled to 30-45 minutes to obtain a uniformly infiltrated hybrid solid electrolyte membrane.
7. The method for processing a solid-state battery pack according to claim 1, characterized in that: The step of heat treating and stress regulating the uniformly infiltrated hybrid solid electrolyte membrane to obtain a structurally stable hybrid solid electrolyte membrane comprises: Obtain stress distribution data of the uniformly infiltrated hybrid solid electrolyte membrane, and when the local stress value is greater than 2MPa, set the heat treatment temperature of the corresponding area to 60-65°C, and when the local stress value is less than 2MPa, set the heat treatment temperature of the corresponding area to 50-55°C, and the heat treatment time is 4-6 hours to obtain a hybrid solid electrolyte membrane with thermal stress release; According to the ion conductivity distribution data of the hybrid solid electrolyte membrane with thermal stress release, selective microwave irradiation is performed on the area with ion conductivity lower than 0.5 mS / cm, the microwave frequency is controlled to be 2.45 GHz, the power density is 0.8-1.2 W / cm², and the irradiation time is 10-15 minutes to obtain a hybrid solid electrolyte membrane with ion channel activation; Under an inert atmosphere, based on the stress distribution data in the thickness direction of the ion channel-activated hybrid solid-state electrolyte membrane, a prestress field is applied to the ion channel-activated hybrid solid-state electrolyte membrane, the compressive stress parallel to the membrane surface is controlled to be 0.6-0.8MPa, and the tensile stress perpendicular to the membrane surface is controlled to be 0.3-0.4MPa. The prestress is maintained for 2-3 hours to obtain a structurally stable hybrid solid-state electrolyte membrane.
8. The method for processing a solid-state battery pack according to claim 1, characterized in that: The nano-interface layer is constructed on the surface of the self-supporting electrode, and the structurally stable hybrid solid electrolyte membrane is laminated with the self-supporting electrode to obtain a flexible solid-state battery pack, comprising: Under an inert atmosphere, lithium titanate is dissolved in isopropanol, polyvinylidene fluoride-hexafluoropropylene copolymer is added as a binder, the mass ratio of the lithium titanate to the polyvinylidene fluoride-hexafluoropropylene copolymer is controlled to be 4:1, after being stirred evenly, spin-coated on the surface of a self-supporting electrode, and dried at 80° C. for 2 hours to obtain a self-supporting electrode with a nano interface layer; The structurally stable hybrid solid electrolyte membrane is attached to the surface of the self-supporting electrode with the nano interface layer, and hot pressing is performed under an inert atmosphere by temperature-pressure coordinated control, wherein the hot pressing temperature is 70-80° C., the pressure is 2-3 MPa, and the holding time is 30-40 minutes to obtain a first electrode laminate structure; preparing a second self-supporting electrode having a nano interface layer, and laminating the second self-supporting electrode having a nano interface layer with the first electrode laminate structure using the same lamination process as the first electrode laminate structure to obtain an electrode-electrolyte-electrode laminate structure; A UV-curable epoxy resin sealing layer is coated on the peripheral area of the laminated structure, and ultraviolet light is irradiated in an inert atmosphere, the light intensity is controlled to be 80-100mW / cm², and the irradiation time is 5-8 minutes to obtain a flexible solid-state battery pack.
9. A solid-state battery pack, characterized in that: The solid-state battery pack is prepared by using the processing method of the solid-state battery pack according to any one of claims 1 to 8.
Citation Information
Patent Citations
Flexible lithium-ion battery
CN112673491A
Preparation method of electric-field-induction-driven ionic electroactive polymer and application
CN113278195A
Preparation method of high-interface-strength fiber composite material
CN113638228A
Solid electrolyte and preparation method and application thereof
CN114759256A
Composite solid electrolyte membrane, preparation method thereof and all-solid-state lithium metal battery
CN114927753A